The Factor That Influences Consumers’ Buying Intention of Electric Vehicle (EV) In Malaysia - Wen Yan, Chu; Pakir Mohamed, Mohamed Ismail (Research in Management of Technology and Business, 2022)
With growing attention to global warming and the concern of potential future raises in gas and petroleum costs, few automobile manufacturers have started producing electric vehicles (EVs) and have gradually entered the market in recent years. These had raised the buying intention of EVs among the people. This study aims to determine the most influential factor and to evaluate the level of consumers’ acceptance of electric vehicles (EVs) which affects consumers’ buying intention toward electric vehicles (EVs) in Malaysia. In this research, the non-random sampling technique was used. The questionnaires were distributed to 100 respondents who are 18 years old and above 60 years old who have jobs and salary payments in Malaysia through an online Google form and IBM Statistical Package Social Science (SPSS) software was used to analyze the data. The results of this study revealed that social media, celebrity, facilitating condition, feature and design, price value, and environmental concern have a positive influence on consumers’ buying intention of electric vehicles (EV). To conclude, among all the IVs, feature, and design (FD) has the most significant and strongest influence on consumers’ buying intention of EV; whereas facilitating condition (FC) is the weakest.